Effect of gold nanoparticles and ciprofloxacin on microbial catabolism: a community‐based approach. (22nd November 2013) - Weber, Kela P.; Petersen, Elijah J.; Bissegger, Sonja; Koch, Iris; Zhang, Jun; Reimer, Kenneth J.; Rehmann, Lars; Slawson, Robin M.; Legge, Raymond L.; O'Carroll, Denis M.
Abstract The effect of gold nanoparticles (AuNPs) and ciprofloxacin on the catabolism of microbial communities was assessed. This was accomplished through an ex situ methodology designed to give a priori knowledge on the potential for nanoparticles, or other emerging contaminants, to affect the catabolic capabilities of microbial communities in the environment. Microbial communities from a variety of sources were incubated with 31 prespecified carbon sources and either National Institute of Standards and Technology reference material 10‐nm AuNPs or ciprofloxacin on 96‐well microtiter plates. From the ciprofloxacin study, dose−response curves were generated and exemplified how this method can be used to assess the effect of a toxicant on overall catabolic capabilities of microbial communities. With 10‐nm AuNPs at concentrations ranging from 0.01 µg/mL to 0.5 µg/mL, rhizosphere communities from Typha roots were only slightly catabolically inhibited at a single concentration (0.05 µg/mL); no effects were seen on wetland water communities, and a minor positive (i.e., enhanced catabolic capabilities) effect was observed for loamy soil communities. This positive effect might have been because of a thin layer of citrate found on these AuNPs that initiated cometabolism with some of the carbon sources studied. Under the conditions considered, the possible adverse effects of AuNPs on the catabolic capabilities of microbial communities appears to be minimal. Environ Toxicol Chem 2013;33:44–51. © 2013 SETAC